PENGARUH GOOD CORPORATE GOVERNANCE, LEVERAGE, MAQASHID SHARIA, EARNING PER SHARE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Pada Bank Umum Syariah di Indonesia Periode 2016-2020) - Junaidi Junaidi (MAGISTER MANAJEMEN UNISMA, 2022)
This study aims to determine the effect of Good Corporate Governance, , Leverage, Maqashid Sharia, Earnings Per Share and Profitability to Economic Value Added at Indonesian Islamic Commercial Banks registered in the Financial Services Authority (OJK) for the 2016-2020 period, with purposive sampling technique for islamic commercial banks in 2016-2020 and using multiple linear regression analysis. The results showed that the Good Corporate Governance, leverage and earnings per share has a significant positive effect on Economic Value Added. Maqashid Sharia has no effect on Economic Value Added. Profitability has no effect on Economic Value Added.Keywords : Good Corporate Governance, Leverage, Maqashid Sharia, Earnings Per Share, Profitability and Economic Value Added